2014
DOI: 10.4238/2014.february.13.2
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of the MHM region and of sex-determining-related genes during gonadal development in chicken embryos

Abstract: ABSTRACT. The chicken (Gallus gallus) embryo has been used as a classic model system for developmental studies because of its easy accessibility for surgical manipulation during embryonic development. Sex determination in birds is chromosomally based (ZZ for males and ZW for females); however, the basic mechanism of sex determination is still unknown. Here, the dynamics of expression of candidate genes implicated in vertebrate sex determination and differentiation were studied during embryonic chicken gonadal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
16
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 34 publications
(40 reference statements)
1
16
0
1
Order By: Relevance
“…In a recent study of brazilian geneticists that used variant of RT-PCR was shown that the largest transcription of MHM for the analyzed period of incubation (4 -14 days) is detected at 8 and 14. The males in the absence of transcription of this gene show an intense activity of DMRT1 [38]. Results of work once again confirm the participation of RNA MHM in differential regulation of male and female alleles of DMRT1 gene.…”
Section: Sexual Differentiation In Birdssupporting
confidence: 70%
“…In a recent study of brazilian geneticists that used variant of RT-PCR was shown that the largest transcription of MHM for the analyzed period of incubation (4 -14 days) is detected at 8 and 14. The males in the absence of transcription of this gene show an intense activity of DMRT1 [38]. Results of work once again confirm the participation of RNA MHM in differential regulation of male and female alleles of DMRT1 gene.…”
Section: Sexual Differentiation In Birdssupporting
confidence: 70%
“…Sharing an overall identity of 67% at the amino acid level and up to 90% identity when specifically considering the HMG DNA‐binding domain, the X‐chromosomal SOX3 ‐encoded protein is most similar to SRY . Consistent with this hypothesis, the expression of SOX3 has been documented in the developing gonads of mice, chicken , fish , and frog . Only the absence of SOX3 expression in the developing marsupial gonad is not consistent with a conserved role in mammalian sex determination .…”
Section: Master Sex‐determining Genes: Case Studies From Sox and Dm Dmentioning
confidence: 95%
“…Given that it is situated within the oldest portion of the avian sex chromosomes (Zhou et al 2014), it may be that selection for dosage compensation has simply had longer to act on this region, in a similar way to the more complete dosage compensation on the older regions of the therian X chromosome (Carrel and Willard 2005). In contrast, on the basis of coexpression patterns, others have suggested that the MHM locus is a regulator of DMRT1 (Yang et al 2010b;Caetano et al 2014), the major avian sex-determining gene (Smith et al 2009), which is located nearby on the Z chromosome. Therefore, the distinct sex-specific regulatory pattern of genes in this region instead may reflect an important role in sex-specific fitness and sexual differentiation.…”
mentioning
confidence: 93%